Economical fabrication of graphite/paper-based humidity sensor - Shuthish Elangkovan; Mastura Shafinaz Zainal Abidin; Shaharin Fadzli Abd Rahman; Mohammad Shafiq Che Soh; Ahmad Bukhairi Md Rashid (Institute of Advanced Engineering and Science, 2020)
Paper is regarded as a promising alternative for low-cost and biodegradable substrate. Paper can be a very good humidity detecting substrate due to its capability to absorb water vapour, thanks to its porous surface. This work explores the feasibility of developing a paper-based humidity sensor using simple and low cost fabrication process. Two type of electrode structures, namely interdigitated and parallel electrode, were formed by using two different pencil grade. The pencil grades used were 2B and 6B. The current-voltage (I-V) characteristics of the fabricated device were measured under different relative humidity and its humidity sensing operation was analyzed. It was observed that the sensor with the 6B and parallel electrode configuration was the most responsive to humidity changes while the 6B interdigitated sensor was the second best. The sensors fabricated with the 6B electrodes are better at sensing humidity changes compared to the sensors fabricated using 2B electrodes.